0176 Developing A Community Simulated Placement For Pre-registration Undergraduate Nurses. (1st November 2014) - Fordham-Clarke, Carol; Zeller, Irene; Burke, Michelle
Abstract : Background: Government policy has increasingly focused on care being delivered to patients closer to home (DH 2007). To ensure compassion remains at the forefront of nursing in any health care setting it was considered important to increase student nurse's exposure to community nursing care. In order to meet this need in the undergraduate pre-registration nursing programme we developed one week simulated placement with a community nursing focus. This was undertaken by all 1st year adult undergraduate nurses at the end of the academic year. Students will then undertake an actual community placement in year 2 of their programme. Methodology: This was developed in line with NMC guidelines (2007) for simulated placements. Utilising patient scenarios students were encouraged to develop skills and behaviours in a safe environment and explore how these are transferred to practical situations. Examples included: Exploring the skills required to make a comprehensive assessment of the patient requiring nursing care at home Adapting wound care and aseptic technique in the home environment Developing communication skills of motivational interviewing to influence lifestyle changes Promoting communication skills to enable the dying patient and their family experience a good death Assessing a patient with respiratory disease and facilitating effective use of inhaler therapies. This innovation was facilitated by liaison with specialist community academic and clinical colleagues and the development of a simulated home room within the skills centre. Results: Student evaluations have been overwhelmingly positive both for individual sessions and for the placement. Students have welcomed the insight into community care; valuing greater contact with specialist nurses and the ability to apply knowledge and skills gained in the classroom to clinical care (Draper 2006). Conclusions: We hope to question students following their actual placement to ascertain if the simulated placement was considered beneficial to their experience. References: Department of Health, (2007) Shifting care closer to home. DH, London Draper J. Editorial: Nurse education: time to get it right. J Clin Nurs 2006;16(9):1069–1070 Nursing and Midwifery Council, (2007) Supporting direct care through simulated practice learning in the pre-registration nursing programme NMC Circular 36/2007 NMC: London